National medical service
1943-10-20 1943 1940s 15 pages -5- 12. Medical Research. This is another important section of the National Health Services which call for review, and for a closer association with the practising members of the profession. At present Medical Research tends to rather aloof, reserved, separate from the professional ranks in an assumed hierarchy of its own. National Medical Research utilising public funds is in the hands of the Medical Research Council theoretically under the Privy Council but in reality an autonomous semi-authoritative unsupervised body, pursuing its own policy and direction. It is a body of mixed professional and lay members, not linked up in any way surprisingly with the work of the Ministry of Health. Its members consist of scientific, medical, and lay members. One of the lay members is an M.P. nominated by the Crown. There is no representative of the organised T.U. Movement, and except for its annual report, not written for popular appeal or interest it has few contacts with the lay public, or the professional ranks. As a result there is a persistent lag between the beneficial announcement of a tested medical research, culminating in a definite treatment or investigatory recommendation and actual medical practice, between the finished research and its marked or full use. The Medical Research Council has one useful subsidiary - the Industrial Health Research Board, the members of which, though personally selected, represent most sections of the public. It has usually representatives of the Factory Medical Department, Medical Officers of Industrial firms and a member of the T.U. movement. Its scope is very wide and as its annual reports indicate, useful work has been done. In addition, private medical research, either personal or endowed, continues in medical institutions or teaching schools without any public supervision (except under the Anti-Vivisection Act with a single sinecure itinerant inspectorship) or inter-institutional co-operation, so that such researches are pigeonholed by themselves till the results are announced. Again private, voluntary or personal research institutes are established out of funds provided by a private philanthrophist for any one special or series of particular researches. And all the while the chemical firms are conducting more or less extensive experiment and researches with different newly discovered chemical combinations or drugs, with its effects on animals before being passed into circulation for trial and use in medical institutional or private practice. Medical Research is therefore at this stage like any other aspect of Medical Practice without cohesion or planned linkage. A well planned joint Chemical and Medical Authority Research Body, with a definite policy would be of considerable advantage. And such a body should be an important adjunct of the National Health Service in a co-ordinated Administration in a Health Ministry. 13. The Medical Services themselves may be considered from five aspects. (A) The Medical Institutions, including the subsidiary ones such as Convalescent Romes. (B) The General Medical Practitioners of "average skill and ability" for giving advice and treatment to sick persons at their homes, or for cases able to travel or work (ambulant cases), treatment etc. at the doctor's surgery or clinic at appointed hours. (C) Consultant or specialists with up-to-date special knowledge to provide service for cases dealt with by the practitioners who will seek advice from the appropriate consultant at meetings at the patients' home or clinic or doctor's surgery. 292/847/2/113